Association between genetic variants of serotonergic and glutamatergic pathways and the concentration of neurometabolites of the anterior cingulate cortex in paediatric patients with obsessive–compulsive disorder. (3rd July 2016) - Ortiz, Ana E.; Gassó, Patricia; Mas, Sergi; Falcon, Carles; Bargalló, Nuria; Lafuente, Amalia; Lázaro, Luisa
Abstract: Objectives : The present study aimed to assess the relationship between variability in genes related to the pathophysiology of obsessive–compulsive disorder (OCD) and the concentration of different neurometabolites in the anterior cingulate cortex (ACC). Methods : We concomitantly assessed neurometabolite concentrations using 3-T 1 H-MRS and 262 single nucleotide polymorphism (SNPs) in 35 genes in 41 paediatric OCD patients. Results : There were significant associations, after Bonferroni correction, between the concentration of inositol, glutamate and glutamine, and total choline and five polymorphisms located in genes related to serotonin and glutamate (i.e., the vesicular monoamine transporter 1 gene, SLC18A1 [rs6586896]; the serotonin receptor 1B gene, HTR1B [rs6296 and rs6298]; and the glutamate receptor, ionotropic, AMPA1 gene, GRIA1 [rs707176 and rs2963944]). Conclusions : The association observed between these polymorphisms and the neurometabolite concentrations could indicate the presence of a biological interaction between the serotonin and the glutamate pathways that could be involved in the pathophysiology of OCD. More studies with this methodology could increase our understanding of the aetiology and pathophysiology of OCD in children.